A Salt‐in‐Metal Anode: Stabilizing the Solid Electrolyte Interphase to Enable Prolonged Battery Cycling. (3rd March 2021) - Fu, Lin; Wang, Xiancheng; Wang, Li; Wan, Mintao; Li, Yuanjian; Cai, Zhao; Tan, Yuchen; Li, Guocheng; Zhan, Renming; Seh, Zhi Wei; Sun, Yongming
Abstract: Metallic lithium (Li) is the ultimate anode candidate for high‐energy‐density rechargeable batteries. However, its practical application is hindered by serious problems, including uncontrolled dendritic Li growth and undesired side reactions. In this study a concept of "salt‐in‐metal" is proposed, and a Li/LiNO3 composite foil is constructed such that a classic electrolyte additive, LiNO3, is embedded successfully into the bulk structure of metallic Li by a facile mechanical kneading approach. The LiNO3 reacts with metallic Li to generate Li + conductive species (e.g., Li3 N and LiN x O y ) over the entire electrode. These derivatives afford a stable solid electrolyte interphase (SEI) and effectively regulate the uniformity of the nucleation/growth of Li on initial plating, featuring a low nucleation energy barrier and large crystalline size without mossy morphology. Importantly, these derivatives combined with LiNO3 can in‐situ repair the damaged SEI from the large volume change during Li plating/stripping, enabling a stable electrode‐electrolyte interface and suppressing side reactions between metallic Li and electrolyte. Stable cycling with a high capacity retention of 93.1% after 100 cycles is obtained for full cells consisting of high‐loading LiCoO2 cathode (≈20 mg cm −2 ) and composite metallic Li anode with 25 wt% LiNO3 under a lean electrolyte condition (≈12 µL) at 0.5 C. Abstract : A "salt‐in‐metal" composite Li anode is fabricated by introducing LiNO3 into the bulk of metallic Li using a simple mechanical kneading approach at room temperature. The coexistence of LiNO3 and its derivatives helps to construct a stable solid electrolyte interphase and regulates uniform plating/stripping of metallic Li, hence enabling a much improved cycle life under a lean carbonate electrolyte condition.